STRATEGIC MANAGEMENT FOR HOLISTIC DEVELOPMENT IN ISLAMIC EARLY CHILDHOOD EDUCATION - Istikomah, Istikomah; Novita, Mona; Purwanti, Purwanti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze the holistic management strategy based on Islamic values that can be applied in schools to improve the quality of early childhood education. This study uses a qualitative case study approach with interviews, observation, and documentation techniques to collect data from the principal, teachers, and parents. The study results indicate that a strong partnership between schools, parents, and the community plays a vital role in creating an environment that supports the overall development of children. An open and communicative internal school environment contributes to an effective learning process despite limited access to more modern external facilities. The holistic curriculum implemented at RA Alam Ya Bunayya covers children's cognitive, social, emotional, and character aspects, emphasizing character development and social habits. These findings indicate that strengthening partnerships with parents and the community can improve the quality of education and child development. At the same time, increasing access to external resources is needed to support the implementation of a more innovative and technology-based curriculum.